Sex/Machine Readings in Culture, Gender, and Technology - Hopkins, Patrick D. (Indiana University Press, 1998)
As powerful interacting social and physical forces, gender and technology shape our experiences, cultures, and identities-sometimes in such comfortable and subtle ways that it takes effort to appreciate them; sometimes in such conspicuous and explosive ways that everyone recognizes their importance. Delving into these issues is an opportunity to discover how technology promises or threatens to rewrite our ideas about sex, sexuality, and gender identity.